Generation and Fusion of Human Cortical and Medial Ganglionic Eminence Brain Organoids. (11th September 2018) - Xiang, Yangfei; Yoshiaki, Tanaka; Patterson, Benjamin; Cakir, Bilal; Kim, Kun‐Yong; Cho, Yee Sook; Park, In‐Hyun
Abstract: Three‐dimensional brain organoid culture has become an essential tool for investigating human brain development and modeling neurological disorders during the past few years. Given specific regionalization during brain development, it is important to produce distinct brain organoids that represent different brain regions and their interactions. The authors recently established a platform to generate brain organoids resembling the medial ganglionic eminence (MGE), a specific brain region responsible for interneurogenesis, and found that when these organoids were fused with organoids resembling the cortex, the resulting organoids enabled modeling of interneuron migration in the brain. This unit describes four basic protocols that have been successfully applied by the authors, covering the generation of embryonic bodies with neuroectodermal fate, the production of human MGE organoids and cortical organoids, and the fusion of these two organoids. © 2018 by John Wiley & Sons, Inc.